(untitled) (Journal of Medical & Health Sciences Review, 2025)
Reflective writing is an essential component of learning, allowing students to synthesize theoretical knowledge and practical experience. This journal recounts an educational experience during the Advanced Specialty Practicum: Education at Aga Khan University, Karachi, where the author engaged in an authentic skills-based assessment of pediatric nursing students. The assessment involved evaluating students on clinical skills such as baby bathing and IV medication administration. The experience highlighted the challenges students faced in executing skills efficiently within a structured time frame and emphasized the role of rubrics in objective grading. The author’s initial unfamiliarity with Likert-scale evaluations led to critical self reflection, improvement through feedback, and a deeper understanding of authentic assessment principles. The guidance of an experienced preceptor played a crucial role in refining evaluation techniques. This reflective process underscored the significance of formative and summative assessments in nursing education, ensuring competency-based learning. Moreover, it reinforced the value of experiential learning as an effective educational strategy. Moving forward, the author aims to integrate these insights into future teaching practices, emphasizing structured evaluation, constructive feedback, and experiential learning to enhance student competency and confidence in clinical settings.